2005
DOI: 10.1007/s11124-005-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Long-term Corrosion of Bronze Artefacts in Soil

Abstract: The investigation was undertaken to determine the main factors causing deterioration of bronze objects in soil by studying artefacts from archaeological excavations in progress. Objects that had been buried for 300-3000 years were examined. The composition of the metal, corrosion products, and surrounding soil was determined by chemical analysis. The possible effect of polluting sources and the environment in general was also taken into account. In total, 82 variables were coded, and their effects were statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 8 publications
0
43
0
1
Order By: Relevance
“…Nord et al [20,21] suggested an estimating factor to represent corrosion severity in archaeological copper alloy objects, named as the degree of deterioration (Fdet). They classified the objects in five groups regarding to the volume of corrosion occurred and observed in the cross section of copper alloy objects.…”
Section: Estimation Of Degree Of Deterioration (Fdet)mentioning
confidence: 99%
See 4 more Smart Citations
“…Nord et al [20,21] suggested an estimating factor to represent corrosion severity in archaeological copper alloy objects, named as the degree of deterioration (Fdet). They classified the objects in five groups regarding to the volume of corrosion occurred and observed in the cross section of copper alloy objects.…”
Section: Estimation Of Degree Of Deterioration (Fdet)mentioning
confidence: 99%
“…Then the soil corrosivity is classified into four groups: non-corrosive (0-10), partially corrosive (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), corrosive (21-30) and severely corrosive (31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Figure 5 shows the columnar diagram of soil corrosivity index of the soil samples analysed in two archaeological sites.…”
Section: Soil Corrosivitymentioning
confidence: 99%
See 3 more Smart Citations